Thinking Ability of Teacher Questions on Indonesian Language Learning - Andi Rurisfiani; Ramly Ramly; Sultan Sultan (Bahasa: Jurnal Keilmuan Pendidikan Bahasa dan Sastra Indonesia, 2019)
Analysis of Teacher Questions with the Framework of LOTS (Lower Order Thinking Skills) and HOTS (High Order Thinking Skills) on Indonesian Language Learning in Soppeng Vocational High School 3. This study aims to describe the form of LOTS and HOTS teacher questions at the beginning, middle, and end of Indonesian Language learning at Soppeng State Vocational High School 3 using the Bloomers & Anderson Revision Taxonomy guide. The analysis in this study is a quantitative descriptive study. The techniques used in data collection are record and technique notes. The technique used to analyze data in this study is descriptive statistics. The results of the study indicate that at the beginning and end of learning there are 100% low-level questions (LOTS). At the core of learning, 89.72% of low-level questions and as many as 10.28% of questions belong to the category of high-level questions (HOTS).